0805 Sleep Related Dysfunction in Children with Autonomic Disorders. (27th April 2018) - Barzilai, J; Bierer, D; Thomas, C; Gisela, C; Bandla, H
Abstract: Introduction: Autonomic Nervous system has intricate anatomical, physiological and neurochemical relationships with Sleep-Wake regulation. Adults with autonomous dysfunction report insomnia, day time fatigue and sleepiness. Limited data are available on sleep in children with autonomic disorders. Aim of this study was to estimate the prevalence of sleep problems in children with autonomic dysfunction. Methods: This was an IRB approved Protocol.Charts were retrospectively reviewed from the Autonomic Disorders Clinic at Children's Hospital of Wisconsin. Children with positive autonomic testing were enrolled in the study. Children were divided into Postural Orthostatic Tachycardia Syndrome(POTS), and Orthostatic hypotension, Orthostatic Intolerance, Pre-Syncope(Non-Pots). Subjects completed a validated Pediatric Sleep Questionnaire(PSQ) and Fatigue Severity Scale questionnaire(FSS) at the clinic visit. PSQ items were grouped into Sleep Related Breathing Disorder(SRBD) scale, Periodic Limb Movement(PLMD) scale, Insomnia scale and Sleepiness scale. Scores of>0.33 for each subscale were considered abnormal.FSS scores of greater than 4 were considered as abnormal. Results: A total of 32 children(POTS: NONPOTS=17:15) were eligible for inclusion in the study. Mean age was 14.9 years(range: 6–17).M: F=5:27. Mean fatigue score was4.68 ± 1.3(SD)*, Mean SRBD score was0.28 ± .11(SD), Mean PLMD Score was0.53 ± .25(SD)*, Mean Insomnia score was 0.52 ± .30(SD)* and Mean Sleepiness Scale score was 0.63 ± .20(SD)*. (*=abnormal). Sub Group Analysis: Mean Scores(SD) for POTS vs Non POTS group : FSS scores: 4.84 ± 1/ 4.55 ± 1(p:0.52), SRBD scale: 0.33 ± 1/ 0.25 ± .08(p:0.06), PLMD scale:0.57 ± .23/0.49 ± .26(p:0.47), insomnia Scale:0.52± .30/0.42 ± 0.30(p:0.31)and Sleepiness scale 0.63 ± .15/. 0.62 ± .24 (p:0.71). Thus, statistically significant differences were not observed between the two groups. Conclusion: 1.Children with autonomic disorders have positive scores on Fatigue Severity Scale, PLMD scale, Insomnia scale and Sleepiness scale, suggestive of higher risk for fatigue, day time sleepiness, non-restorative sleep and PLMD. 2) Sleep dysfunction is prevalent equally in all children with autonomic dysfunction with no differences between POTS and NON POTS sub groups. Support (If Any): Supported by an from Advancing Healthier Wisconsin (AHW) Grant # 5520298, T Chelimsky (PI).